MENGURANGI GEJALA FEAR OF MISSING OUT (FOMO) PADA SISWA MELALUI PSIKOEDUKASI DALAM LAYANAN BIMBINGAN KLASIKAL - Endri Irawan; Dina Hidayati Hutasuhut; Syarif Maulidin (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
ABSTRACT The phenomenon of Fear of Missing Out (FOMO) has become increasingly prominent among adolescents, particularly due to the intensive use of social media. FOMO negatively impacts mental health, leading to issues such as anxiety, academic stress, and impaired concentration in learning. This study aims to determine the effectiveness of classroom guidance services based on psychoeducation in reducing FOMO symptoms among high school students. The method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, consisting of two cycles. The research subjects were 25 eleventh-grade students at Alwashliyah Senior High School in Medan, who exhibited moderate to high levels of FOMO based on pretest results. Data collection instruments included a FOMO questionnaire adapted from the scale developed by Przybylski et al. (2013), participatory observation, and informal interviews. The results showed a decrease in FOMO scores from 72.4 (high category) before the intervention, to 61.2 (moderate category) after the first cycle, and 50.8 (low category) after the second cycle. This reduction indicates that psychoeducational-based classroom guidance services are effective in raising students’ awareness of the impacts of FOMO and equipping them with self-management strategies for social media use. These findings support the importance of integrating psychoeducational approaches into school counseling programs to enhance students’ psychological well-being in the digital era. ABSTRAK Fenomena Fear of Missing Out (FOMO) menjadi isu yang semakin menonjol di kalangan remaja, terutama akibat penggunaan media sosial yang intensif. FOMO berdampak negatif terhadap kesehatan mental, seperti kecemasan, stres akademik, dan gangguan konsentrasi belajar. Penelitian ini bertujuan untuk mengetahui efektivitas layanan bimbingan klasikal berbasis psikoedukasi dalam mengurangi gejala FOMO pada siswa sekolah menengah. Metode yang digunakan adalah Penelitian Tindakan Kelas (PTK) model Kemmis dan McTaggart yang terdiri dari dua siklus. Subjek penelitian adalah 25 siswa kelas XI SMA Alwashliyah Medan dengan tingkat FOMO sedang hingga tinggi berdasarkan hasil pretest. Instrumen pengumpulan data mencakup angket FOMO yang dimodifikasi dari skala Przybylski et al. (2013), observasi partisipatif, dan wawancara informal. Hasil penelitian menunjukkan adanya penurunan skor FOMO dari 72,4 (kategori tinggi) sebelum tindakan, menjadi 61,2 (kategori sedang) setelah siklus I, dan 50,8 (kategori rendah) setelah siklus II. Penurunan ini menunjukkan bahwa layanan bimbingan klasikal berbasis psikoedukasi efektif dalam meningkatkan kesadaran siswa mengenai dampak FOMO dan membekali mereka dengan strategi pengelolaan diri dalam penggunaan media sosial. Temuan ini mendukung pentingnya integrasi pendekatan psikoedukatif dalam program bimbingan dan konseling di sekolah untuk meningkatkan kesejahteraan psikologis siswa di era digital.